INDIRECT METHODS OF SELECTION IN WINTER WHEAT BREEDING ON BASIS OF GENETIC CORRELATIONS - Tishchenko, V. N.; Batashova, М. Е.; Shapochka, О. М. (Scientific Progress & Innovations, 2014)
З метою покращення селекційного процесу на про- дуктивністю були вивчені кореляції між врожайніс- тю та рядом ознак та індексів у 170 ліній озимої пшениці. Для пошуку найбільш ефективних методів оцінки зразків ми провели порівняння мінливості ге- нетичних та екологічних кореляцій. Використання таких індексів як атракції (маса зерна з колосу / маса колосу), мікророзподілень (маса зерна з колосу / маса полови колосу) та полтавський індекс (маса зерна з колосу / довжина верхнього міжвузля) у непрямому доборі на ранніх етапах селекції озимої пшениці за- безпечить ефективну селекцію на високу продуктив- ність колосу. Одержані результати вказують на мінливість ознак та індексів в залежності від гено- типу, гомозиготного чи гетерозиготного стану. Для підвищення ефективності добору важливим є пошук фенотипових кореляцій, де генетичний компонент направлений в одному напрямку, а екологічний в про- тилежному або близький до нуля. Коефіцієнти коре- ляції збільшуються під впливом лімітуючих зовнішніх факторів та зменшуються в комфортних умовах для росту і розвитку рослин озимої пшениці. With the aim to improved breeding process for productivity, correlations among yield and a number of traits and indexes in 170 winter wheat lines have been investigated. For searching the most effective methods of estimating accessions we have used comparison of genetic and ecological correlations variability. The application of such indexes as attraction index (weight of spike, g / weight of stem, g), microdistribution index (weight of grains in spike, g / weight of spike chaff ) and poltavskiy index (weight of grains in spike, g / apical internode length, sm) in indirect selection on the early winter wheat breeding will provide effective breeding for high spike productivity. The obtained results indicate at the variability of traits and indexes depending on the genotype, homo- or heterozygote state. For increasing the efficiency of selection it is very important to find phenotype correlations where the genetic component is directed one way and the ecological is opposite or near zero. Correlation coefficients increased under the influence of limiting environment factors and decreased in comfortable conditions for growth and development of winter wheat plants.